2017
DOI: 10.1016/j.acap.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences and ADHD Diagnosis at Age 9 Years in a National Urban Sample

Abstract: Objective To examine associations between adverse childhood experiences (ACEs) and attention-deficit/hyperactivity disorder (ADHD) at age 9 years using longitudinal data and assess the extent to which ACEs during middle childhood are independently associated with ADHD at age 9 years. Methods We conducted a secondary analysis of data from the Fragile Families urban birth cohort 5- and 9-year interviews. The sample was limited to children for whom mothers were the primary caregiver and mother-reported informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 33 publications
2
39
0
1
Order By: Relevance
“…More recent research demonstrates that adversity specifically in the form of neglect, but not abuse, is related to cognitive dysfunction [4][5][6] . During the adolescent years, such adverse experiences even manifest as attention-deficit hyperactivity disorder (ADHD) 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…More recent research demonstrates that adversity specifically in the form of neglect, but not abuse, is related to cognitive dysfunction [4][5][6] . During the adolescent years, such adverse experiences even manifest as attention-deficit hyperactivity disorder (ADHD) 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, ACE is more likely to cause future mental illnesses, such as depression, schizophrenia, and attention deficit hyperactivity disorders (ADHD), and negative emotions, such as depression and anxiety. 3 , 4 In addition, studies have shown that ACEs are associated with physical inflammation and other physical health conditions. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Adverse childhood experience has been identified to relate to attention deficit hyperactivity disorder (ADHD) [13, 17, 18]. It was found that children who experienced socioeconomic hardship, parental divorce, familial mental illness, neighborhood violence, and incarceration had higher risk for ADHD [18].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that children who experienced socioeconomic hardship, parental divorce, familial mental illness, neighborhood violence, and incarceration had higher risk for ADHD [18]. Individuals who reported more ACE exposures were more likely to experience the symptoms of ADHD [17, 18]. Furthermore, a significant association between ADHD and depressive symptoms has also been found.…”
Section: Introductionmentioning
confidence: 99%